1998
DOI: 10.1182/blood.v91.9.3127
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fusion Between MOZ and the Nuclear Receptor Coactivator TIF2 in Acute Myeloid Leukemia

Abstract: Chromosomal abnormalities of band 8p11 are associated with a distinct subtype of acute myeloid leukemia with French-American-British M4/5 morphology and prominent erythrophagocytosis by the blast cells. This subtype is usually associated with the t(8;16)(p11;p13), a translocation that has recently been shown to result in a fusion between the MOZ and CBP genes. We have cloned the inv(8)(p11q13), an abnormality associated with the same leukemia phenotype, and found a novel fusion between MOZ and the nuclear rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(61 citation statements)
references
References 38 publications
1
59
0
1
Order By: Relevance
“…Therefore, we subsequently compared the gene expression profile of PCa with and without 8q1 in subsets defined by ETS rearrangements and found that ERG1/8q1 tumors overexpress, in addition to the above-described CDON, also ZNF417 (19q13.43), IKZF2 (2q34), VN1R1 (19q13.4), and NCOA2 (8q13.3). The first two are transcription factors not located in 8q and only IKZF2 has been previously linked to human neoplasias (Carapeti et al, 1998). The VN1R1 gene, on the other hand, has not been previously related to human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we subsequently compared the gene expression profile of PCa with and without 8q1 in subsets defined by ETS rearrangements and found that ERG1/8q1 tumors overexpress, in addition to the above-described CDON, also ZNF417 (19q13.43), IKZF2 (2q34), VN1R1 (19q13.4), and NCOA2 (8q13.3). The first two are transcription factors not located in 8q and only IKZF2 has been previously linked to human neoplasias (Carapeti et al, 1998). The VN1R1 gene, on the other hand, has not been previously related to human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…genes is also known to be involved in the development of leukemia. For example, MOZ or MORF is involved in translocation of AML in the forms of MOZ-CBP, MOZ-p300, MOZ-TIF2 and MORF-CBP (19,(21)(22)(23). TIF2 is also a HAT-associated gene, and all of these translocations retain the HAT domain in involved genes.…”
Section: Discussionmentioning
confidence: 99%
“…This critical role of MOZ was highlighted by a study showing that MOZ mutations introduced in mice resulted in their death at birth, along with impaired hematopoiesis and stem cell development (Thomas and Voss, 2004;Katsumoto et al, 2006;Yang and Ullah, 2007). Furthermore, disruption of the MOZ HAT activity has been linked to the development of disease, particularly leukemia (Carapeti et al, 1998;Crowley et al, 2005;Esteyries et al, 2008).…”
Section: Functional Significance Of the Moz Hatmentioning
confidence: 99%
“…MOZ was first identified as a fusion partner with the CREB binding protein (CBP) HAT in a t(8;16) (p11;p13) translocation found in AML, and disruption of the normal acetylation activity of MOZ leads to leukemogenic transformations and oncogenesis (Borrow et al, 1996). MOZ has also been found translocated to the CBP homolog p300 (Kitabayashi et al, 2001b), to the transcriptional intermediary binding factor 2 (TIF2; Carapeti et al, 1998) and to the nuclear receptor co-activator 3 (NcoA3) transcription factor (Esteyries et al, 2008). The t(8;16)(p11;p13) translocation of MOZ to CBP produces a characteristic gene expression pattern with elevated levels of HOXA9, HOXA10 and MEIS1 (Camos et al, 2006).…”
Section: Role Of Moz In Disease Progressionmentioning
confidence: 99%